Debit Banjir Rancangan DAS Tojo Metode HSS ITB 1 - Aswar Amiruddin; Saparuddin Saparuddin; Triyanti Anasiru (Borneo Engineering : Jurnal Teknik Sipil, 2020)
Floods often occur in several regions in Indonesia. The problem is the flooding with its uncertain characteristics is one of the environmental problems that has not been handled optimally. The method of converting rain data into discharge data for flood analysis has been widely presented in previous studies. The methods used to analyze flood discharge also vary, starting from rational, empirical, statistical models to the unit hydrograph model. This research aims to determine the flood discharge design for return periods 2, 5, 10, 20, 25, 50, and 100 years in Tojo watershed, Tojo Una-una Regency using the synthetic unit hydrograph method of ITB-1. Research methods are data collection and data analysis. Data collection was carried out at several agencies and collecting from online sources. Results of this research design flood discharge that was analyzed by synthetic unit hydrograph of ITB-1 method. The maximum design flood discharge at Tojo watershed are 82.375m3/s for a 2-year, 98.21 m3/s for a 5-year, 104.77 m3/s for a 10-year, 111.83 m3/s for a 20-year, 113.3 m3/s for a 25-year, 118.87 m3/s for a 50-year, 123.86 m3/s for a 100-year return period